1982
DOI: 10.1152/ajprenal.1982.242.6.f705
|View full text |Cite
|
Sign up to set email alerts
|

Tubular handling of Pi in young growing and adult rats

Abstract: The tubular transport of inorganic phosphate (Pi) is controlled by a parathyroid hormone-independent mechanism that responds to variations in the Pi intake. This adaptation mechanism could also respond to growth-mediated variation in the utilization of Pi by the organism. In the present work we have determined the maximal net Pi reabsorption per volume of glomerular filtrate (max TRPi/ml GF) in the young growing (2-mo) and adult 8- to 9-mo) rats. Max TRP[i/ml GF was significantly lower in intact adult (1.44 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The maximal transport was not reached in the basal state, as was indicated by the increase in Pi QR/GFR after the Pi load. In agreement with the reports of Caverzasio et al (4) and Karlen (5) on 2-mo-old rats, the plasma Pi of early weaned 21-d-old rats fed an LPD was higher than that of adult rats, although it was lower than that of control rats of the same age. Pi depletion, which is accompanied by the release of calcium and Pi from bone, may explain the maintained phosphatemia (25).…”
Section: Animalssupporting
confidence: 93%
See 1 more Smart Citation
“…The maximal transport was not reached in the basal state, as was indicated by the increase in Pi QR/GFR after the Pi load. In agreement with the reports of Caverzasio et al (4) and Karlen (5) on 2-mo-old rats, the plasma Pi of early weaned 21-d-old rats fed an LPD was higher than that of adult rats, although it was lower than that of control rats of the same age. Pi depletion, which is accompanied by the release of calcium and Pi from bone, may explain the maintained phosphatemia (25).…”
Section: Animalssupporting
confidence: 93%
“…PiR also increases brush border enzymes over the homogenate activity (Table 4). when growing weaned rats are placed on an LPD (4,5). As in This indicates that the quality of the membrane preparations the adult, the response to change in Pi diet persists when the was not different.…”
Section: Animalsmentioning
confidence: 96%
“…Fractional reabsorption of phosphate is higher in infants than in older children (II). Maximal tubular reabsorption of phosphate per volume glomerular filtration rate is higher in neonatal rats than in adult rats, a difference that persists after thyroparathyroidectomy (12)(13)(14). There is also direct evidence that the higher rate of phosphate reabsorption by the neonate is due in part to a higher intrinsic rate of phosphate reabsorption by the neonatal kidney (15,16).…”
mentioning
confidence: 99%
“…This was seen in rats that received parathyroidectomy indicating that an altered response to parathyroid hormone was not the factor that caused the disparity in renal phosphate uptake [143]. Finally both young and adult rats responded to a low-phosphate diet with an increase in the fractional reabsorption of phosphate; the magnitude of phosphate absorption was again higher in young animals than adults [143].…”
Section: à2mentioning
confidence: 96%
“…Animal studies demonstrated that young rats had a greater rate of phosphate reabsorption than adults [143]. This was seen in rats that received parathyroidectomy indicating that an altered response to parathyroid hormone was not the factor that caused the disparity in renal phosphate uptake [143].…”
Section: à2mentioning
confidence: 99%